2010
DOI: 10.1161/circulationaha.109.926667
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Preconditioning in Human Coronary Artery Bypass Surgery

Abstract: Background-We assessed whether remote ischemic preconditioning (RIPC) improves myocardial, renal, and lung protection after on-pump coronary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
211
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(228 citation statements)
references
References 26 publications
3
211
1
4
Order By: Relevance
“…When these procedures are performed on an elective basis, it may be possible to use some form of remote IPC by induction of HIF-1 in the limb before cardiac surgery, either by transient adenoviral HIF-1α gene therapy, as demonstrated in our study, or by pharmacological inhibition of the prolyl hydroxylases that promote HIF-1α degradation (19). This approach may provide a more robust induction of IL-10 and possibly other protective secreted factors than can be achieved by blood pressure insufflation, which has given mixed results in prospective randomized placebo-controlled clinical trials (12,33).…”
Section: Discussionmentioning
confidence: 79%
“…When these procedures are performed on an elective basis, it may be possible to use some form of remote IPC by induction of HIF-1 in the limb before cardiac surgery, either by transient adenoviral HIF-1α gene therapy, as demonstrated in our study, or by pharmacological inhibition of the prolyl hydroxylases that promote HIF-1α degradation (19). This approach may provide a more robust induction of IL-10 and possibly other protective secreted factors than can be achieved by blood pressure insufflation, which has given mixed results in prospective randomized placebo-controlled clinical trials (12,33).…”
Section: Discussionmentioning
confidence: 79%
“…67 Renal outcomes were among the secondary end points. The results showed that in patients undergoing multivessel coronary artery bypass graft (CABG) surgery, the incidence of AKI in those who received rIPC was similar to that of controls.…”
mentioning
confidence: 99%
“…Оказалось, что ДИП в 10 раз снижает частоту возникновения острого поражения по-чек [49]. Впрочем, некоторым исследователям не удалось обнару-жить ренопротекторный эффект ДИП у пациентов с КШ [50,51]. Кардиохирурги из Великобритании ДИП осуществляли с помо-щью 3 циклов ишемии (5 мин) и реперфузии (5 мин) руки [50].…”
Section: терапевтический архив 8 2016unclassified
“…Впрочем, некоторым исследователям не удалось обнару-жить ренопротекторный эффект ДИП у пациентов с КШ [50,51]. Кардиохирурги из Великобритании ДИП осуществляли с помо-щью 3 циклов ишемии (5 мин) и реперфузии (5 мин) руки [50]. Острое поражение почек они оценивали по необходимости в диа-лизе, по уровню креатина в сыворотке крови, по соотношению альбумин/креатин в моче.…”
Section: терапевтический архив 8 2016unclassified
See 1 more Smart Citation